2021
DOI: 10.1002/path.5679
|View full text |Cite
|
Sign up to set email alerts
|

Salivary glands are a target for SARS‐CoV‐2: a source for saliva contamination

Abstract: The ability of the new coronavirus SARS‐CoV‐2 to spread and contaminate is one of the determinants of the COVID‐19 pandemic status. SARS‐CoV‐2 has been detected in saliva consistently, with similar sensitivity to that observed in nasopharyngeal swabs. We conducted ultrasound‐guided postmortem biopsies in COVID‐19 fatal cases. Samples of salivary glands (SGs; parotid, submandibular, and minor) were obtained. We analyzed samples using RT‐qPCR, immunohistochemistry, electron microscopy, and histopathological anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0
8

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(90 citation statements)
references
References 16 publications
5
77
0
8
Order By: Relevance
“…Results obtained with this study agree with other studies that have ascertained that soon after infection SARS-CoV-2 is abundantly detected in saliva (Pan et al, 2020;Zhu et al, 2020), in line with evidence that indicates that the epithelium associated with the salivary glands is an early site of virus replication (Huang et al, 2021;Matuck et al, 2021;Pascolo et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…Results obtained with this study agree with other studies that have ascertained that soon after infection SARS-CoV-2 is abundantly detected in saliva (Pan et al, 2020;Zhu et al, 2020), in line with evidence that indicates that the epithelium associated with the salivary glands is an early site of virus replication (Huang et al, 2021;Matuck et al, 2021;Pascolo et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…US-guided MITS also allowed us to assess the invasive potential of SARS-CoV-2, with the detection of the virus in various tissues, such as the heart [ 17 , 37 ], intestine and brain [ 17 ], periodontal tissue [ 38 ], and major and minor salivary glands [ 39 ]. These findings have an impact both on the identification of possible viral reservoirs and on understanding the pathophysiology of distinct clinical manifestations.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of SARS-CoV-2 in saliva causes viral proliferation and consequent RNA secretion in any cells involved in the production of salivary components, such as salivary glands, respiratory tract cells, and the periodontal tissue. [27][28] Although our research did not analyze the salivary components and substantivity, we observed a difference in COVID-19 risk in the test community compared to the control community. This was supported by the nding that the virus has been consistently detected in saliva; thus, the oral cavity was a source of SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%